The challenging estimation of trade elasticities: Tackling the inconclusive Eurozone evidence - Sascha Keil (Chemnitz University of Technology, Faculty of Economics and Business Administration, 2021)
This paper sheds light on serious methodological difficulties of employing the empiric export equation in order to derive long-run trade elasticities. The unreliable estimated price coefficient (Kaldor Paradox) and the potential presence of cointegration are identified as the most relevant points. It can be shown that difficulties are in part due to methodological issues. New empirical evidence, encompassing eleven Euro area countries and the timespan 1995- 2019, has been obtained from different cointegration techniques. In seven out of eleven cases a robust long-run relationship can be detected and price elasticity was consistently found being significant and negative.
Keywords: F14; C13; 330; International trade; Competitiveness; Kaldor Paradox; Export equation; ARDL